Arnica montana effects on gene expression in a human macrophage cell line. Evaluation by quantitative Real-Time PCR. Issue 2 (May 2016) - Olioso, Debora; Marzotto, Marta; Bonafini, Clara; Brizzi, Maurizio; Bellavite, Paolo
Abstract : Background: Arnica montana is a popular traditional remedy widely used in complementary medicine, also for its wound healing properties. Despite its acknowledged action in clinical settings at various doses, the molecular aspects relating to how A. montana promotes wound healing remain to be elucidated. To fill this gap, we evaluated the whole plant extract, in a wide range of dilutions, in THP-1 human cells, differentiated into mature macrophages and into an alternative IL-4-activated phenotype involved in tissue remodelling and healing. Methods: Real-time quantitative Reverse Transcription Polymerase Chain Reaction (PCR) analysis was used to study the changes in the expression of a customized panel of key genes, mainly cytokines, receptors and transcription factors. Results: On macrophages differentiated towards the wound healing phenotype, A. montana affected the expression of several genes. In particular CXC chemokine ligand 1 (CXCL1), coding for an chief chemokine, exhibited the most consistent increase of expression, while also CXC chemokine ligand 2 (CXCL2), Interleukin8 (IL8) and bone morphogenetic protein (BMP2) were slightly up-regulated, suggesting a positive influence of A. montana on neutrophil recruitment and on angiogenesis. MMP1, coding for a metalloproteinase capable of cleaving extracellular matrix substrates, was down-regulated. Most results showed non-linearity of the dose-effect relationship. Conclusions: This exploratory study provides new insights into the cellular and molecular mechanisms of action of A. montana as a promoter of healing, since some of the genes it modifies are key regulators of tissue remodelling, inflammation and chemotaxis. Graphical abstract: A possible action of Arnica montana in the mechanisms of the wound-healing process that occurs in dermis and epidermis tissues after an injury. The wound healing process is initiated by the integration of multiple intercellular signals (cytokines and chemokines) released by different kind of cells including macrophages. In this framework the genes for the chemokines CXCL1, CXCL2 and IL8 all were up-regulated by Arnica dilutions in our model of IL-4 treated macrophages. These factors recruit the neutrophils, useful in the process of debris phagocytosis and bacteria killing. A further important role of chemokines is their angiogenic activity through engagement of the common receptor CXCR2. Highlights: Arnica montana is widely used to treat trauma, wounds and post-operative conditions but its action mechanisms are largely unknown. Arnica dilutions 2c, 3c, 5c, 9c, 15c were tested on a human macrophage cell line looking at the expression of inflammatory genes. Treatments caused slight but significant changes in the expression of several genes, often in a non-linear way with various dilutions. In particular the gene CXCL1 exhibited a consistent increase of expression, suggesting a positive influence on cell recruitment and angiogenesis.